Vortex-induced vibration characteristics and suppression device performance on a low mass ratio flexible cylinder [electronic resource] - Lee, Kee Quen, 1987-; Aminudin Abu; Pauziah Muhamad, supervisor; Institut Teknologi Antarabangsa Malaysia - Jepun (2014)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2014